Evaluating conservation threats to reservoirs in the semiarid region of Brazil using the perception of residents - Azevêdo, Evaldo de Lira; Drumond, Maria Auxiliadora; Alves, Rômulo Romeu Nóbrega; Dias, Thelma Lúcia Pereira; Molozzi, Joseline (Ethnobiology and Conservation, 2020)
Conservation and management strategies must be holistic, and therefore must guarantee the participation of local communities in the processes of identifying threats. Our study sought to identify the principal threats to reservoir conservation in the semiarid region of Brazil based on the perception of residents, and develop a conceptual model with the main threats to be used as a basis for orienting conservation measures. The study was undertaken with four communities around four reservoirs in two watersheds. A total of 126 people were interviewed to identify threats to reservoir conservation. The Criticality Index (CI) of threats was calculated based on the methodology developed by Open Patterns for Conservation Practices. Among the principal threats to reservoirs identified by local populations were discharging residues (both solid and liquids) and overfishing. In support of local perception, larger Criticality Index values were recorded for: 1- discharging residues (CI = 0.50), 2- deforestation in the riparian zone (CI= 0.20), and 3 - overfishing (CI = 0.17). The recorded threats put at risk the sustainability of local ecosystems and human populations. It will be necessary to develop effective conservation policies that promote environmental awareness and foster the participation of local communities in the sustainable administration of local ecosystems.